TEORI THE SPREAD OF ISNAD (Telaah Atas Pemikiran Michael Allan Cook) - Ramdhani, Imam Sahal (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
erchange-newline"> It is closely related to â€œCommon Linkâ€ phenomenon whom plenty of West Scholar on Hadith dealing their researches on it. By looking at thisphenomenon, this paper is trying to review Cookâ€™s idea about common linkand the process of theory the spread of isna>d â€˜s aplication in conceivingthe common link phenomenon. Based on this research, we understand thatCook brought a different point of view to the Common Link phenomenonwhich is poured forth on his critics to the Schachtianâ€™s theory. For Cook,there are two essential points related to Common Link. First, Common Linkcanâ€™t be justifid as a hadith counterfeiter. It is because Common Link tosome exctent is an engineering-work from the other narrator (periwayat).Second, Common Link canâ€™t be a basic of hadithâ€™s dating. Then, Cookâ€™spoint of view pulled down Commen Link theory.